2019
DOI: 10.1371/journal.pone.0223764
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of soil pH with geochemical indices in forest soils

Abstract: Soil pH is a critical soil quality index and controls soil microbial activities, soil nutrient availability, and plant roots growth and development. The current study aims to evaluate various pedotransfer functions for predicting soil pH using different geochemical indices (CaO, ratios of Al2O3, Fe2O3, TiO2, SiO2, MgO, and K2O to CaO) in forest soils. Various models including empirical functions (quadratic, cubic, sigmoid, logarithmic) and artificial neural network with these geochemical indices were assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
(22 reference statements)
1
1
0
Order By: Relevance
“…In this study, V was not linearly related to soil pH (data not shown), since soil samples showed a mixed composition of permanent-and variable-charge clay minerals (data not shown) and contained a wide range of OM levels (3.78-79.35 g kg -1 ) (Table 3). This is in line with other findings in literature where relationships between soil pH and V were non-linear, being described by either quadratic (Wang et al, 2019) or sigmoidal models (Kabala and Labaz, 2018;Wu and Liu, 2019). Our results also revealed that the BSAT method overestimated LR to attain pH 5.8 (Figure 4b; Table 4), mostly on soil samples containing T less than 7 cmol c dm -3 , which suggests a contradictory behavior of the method.…”
Section: Methodssupporting
confidence: 92%
“…In this study, V was not linearly related to soil pH (data not shown), since soil samples showed a mixed composition of permanent-and variable-charge clay minerals (data not shown) and contained a wide range of OM levels (3.78-79.35 g kg -1 ) (Table 3). This is in line with other findings in literature where relationships between soil pH and V were non-linear, being described by either quadratic (Wang et al, 2019) or sigmoidal models (Kabala and Labaz, 2018;Wu and Liu, 2019). Our results also revealed that the BSAT method overestimated LR to attain pH 5.8 (Figure 4b; Table 4), mostly on soil samples containing T less than 7 cmol c dm -3 , which suggests a contradictory behavior of the method.…”
Section: Methodssupporting
confidence: 92%
“…To the best of our knowledge, there is a dearth of EA‐PTFs in the published literature. However, there exist PTFs for harmonizing soil pH data to the GlobalSoilMap standard (Libohova et al, 2014) and PTFs for estimation of soil pH from geochemical indices (Wu & Liu, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The soil samples were taken to the laboratory and conditioned for analysis by drying in well-ventilated rooms or in rooms equipped with heating systems up to a temperature of 40 • C, after which they were sieved to a particle size of less than 2 mm. Soil analyses were performed according to the standardized methods: pH was determined potentiometrically in aqueous suspension (10 g of soil/25 mL of bi-distillated water, with a combined pH electrode glass-calomel) [40,41]. Granulometric analysis was performed using the Kacinski method [42].…”
Section: Study Sites and Soil Characteristicsmentioning
confidence: 99%